The Influence of Compensation and Employee Involvement Toward Employee Retention at Jhun Café & Resto: Penelitian - D. T. Kenanga (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Jhun Café & Resto is a business of private company that provide the various food of Tuna Fish. Jhun Café & Resto located at Kawasan Megamas Manado, Sulawesi, Indonesia. Jhun Café & Resto has a problem that is employee turnover. To prevent the turnover, Jhun Café & Resto need the effort of retention strategy. There are many factors that could influence the Employee Retention, therefore the title of this research is The Influence of Compensation and Employee Involvement toward Employee Retention at Jhun Café & Resto. This study aims to find out the influence of Compensation and Employee Involvement toward Employee Retention at Jhun Café & Resto. Type of research is Associative, type of data is Quantitative, method to analyze data is Multiple Linear Regression Analysis and the Population of the employees amounted to 35. The results of the T test obtained that Compensation (X1) ttest = 4.194 > ttable = 2.037. So, Ha accepted and Ho rejected. This means that Compensation partially have influence toward Employee Retention. Employee Involvement (X2) ttest = 1.686 < ttable = 2.037. So, Ha rejected and Ho accepted. This means that Employee Involvement partially have no influence toward Employee Retention. And the result of F test obtained that ftest = 15.507 > ftable = 3.29. So, Ha accepted and Ho rejected. This mean that Compensation and Employee Involvement simultaneous have influence toward Employee Retention.